Getting Engaged: Improving Your Stakeholder Engagement Practices - Kathryn A. Stofer (EDIS, 2017)
This document is part of the Getting Engaged series, which is designed to help Extension and research faculty and other community engagement professionals improve their engagement with a variety of stakeholder audiences. This 4-page document provides basic information that will help faculty and other community professionals become more comfortable with engaging various stakeholder audiences. Written by Kathryn A. Stofer and published by the Department of Agricultural Education and Communication, February 2017.